Treatment and prognosis of patients with urinary bladder cancer with other primary cancers: a nationwide population‐based study in the Bladder Cancer Data Base Sweden (BladderBaSe). (31st August 2020) - Aljabery, Firas; Liedberg, Fredrik; Häggström, Christel; Ströck, Viveka; Hosseini, Abolfazl; Gårdmark, Truls; Sherif, Amir; Jerlström, Tomas; Malmström, Per‐Uno; Hagberg, Oskar; Holmberg, Lars
Abstract : Objective: To study how patients with urinary bladder cancer (UBC) with previous or concomitant other primary cancers (OPCs) were treated, and to investigate their prognosis. Patients And Methods: Using nationwide population‐based data in the Bladder Cancer Data Base Sweden (BladderBaSe), we analysed the probability of treatment with curative intent, and UBC‐specific and overall survival (OS) in patients with UBC diagnosed in the period 1997–2014 with or without OPC. The analyses considered the patient's characteristics, UBC tumour stage at diagnosis, and site of OPC. Results: There were 38 689 patients, of which 9804 (25%) had OPCs. Those with synchronous OPCs more often had T2 and T3 tumours and clinically distant disease at diagnosis than those with UBC only. Patients with synchronous prostate cancer, female genital cancer and lower gastro‐intestinal cancer were more often treated with curative intent than patients with UBC only. When models of survival were adjusted for age at diagnosis, marital status, education, year of diagnosis, Charlson Comorbidity Index and T‐stage, UBC‐specific survival was similar to patients with UBC only, but OS was lower for patients with synchronous OPC, explained mainly by deaths in OPC primaries with a bad prognosis. Conclusions: OPC is common in patients with UBC. Treatment for UBC, after or in conjunction with an OPC, should not be neglected and carries just as high a probability of success as treatment in patients with UBC only. The needs of patients with UBC and OPC, and optimisation of their treatment considering their complicated disease trajectory are important areas of research.